Challenges of stem cell‐based pulp and dentin regeneration: a clinical perspective. Issue 1 (23rd June 2013) - Huang, George T.‐J.; Al‐Habib, Mey; Gauthier, Philippe
Abstract : There are two types of approaches to regenerate tissues: cell‐based and cell‐free. The former approach is to introduce exogenous cells into the host to regenerate tissues, and the latter is to use materials other than cells in an attempt to regenerate tissues. There has been a significant advancement in stem cell‐based pulp and dentin regeneration research in the past few years. Studies in small and large animals have demonstrated that pulp/dentin‐like tissues can be regenerated partially or completely in the root canal space with apical openings of 0.7–3.0 mm using dental pulp stem cells, including stem cells from apical papilla (SCAP) and subpopulations of pulp stem cells. Bone marrow mesenchymal stem cells (BMMSCs) and adipose tissue‐derived MSCs (AdMSCs) have also been shown to regenerate pulp‐like tissue. In contrast, the cell‐free approach has not produced convincing evidence on pulp regeneration. However, one crucial concept has not been considered nor defined in the field of pulp/dentin regeneration and that is the critical size defect of dentin and pulp. Without such consideration and definition, it is difficult to predict or anticipate the extent of cell‐free pulp regeneration that would occur. By reasoning, cell‐free therapy is unlikely to regenerate an organ/tissue after total loss. Similarly, after a total loss of pulp, it is unlikely to regenerate without using exogenously introduced cells. A cell homing approach may provide a limited amount of tissue regeneration. Although stem cell‐based pulp/dentin regeneration has shown great promise, clinical trials are difficult to launch at present. This article will address several issues that challenge and hinder the clinical applications of pulp/dentin regeneration which need to be overcome before stem cell‐based pulp/dentin regeneration can occur in the clinic.